Social Economic Status to the Number of Life Expectancy - Seran, Sirilius (International Journal of Economics and Financial Issues, 2019)
The life expectancy is determined by the social economic status of the population. The intended social economic status includes economic growth, inflation, Gini ratio, dependency ratio, and poverty. The effect of these variables on life expectancy can be partial or simultaneous among the variables. Economic growth can reduce poverty if followed by an equitable distribution. Poverty rate is also worsen by the number of dependency ratio; the productive age population to the young and elderly population. This study is intended to determine the partial relationship, between each variable to population life expectancy, and simultaneous relationships. By using the data time series and cross section for 43 years, based from the Central Bureau of Statistics and several other official sources. Using the path analysis tool, it is known that 43 percent of the life expectancy of the population is simultaneously affected by social economic status. Keywords: Growth, Poverty, Life Expectancy JEL Classifications : C15, J10, O15, O53 DOI: https://doi.org/10.32479/ijefi.8210